A new species of freshwater crab of the genus Teretamon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae) from Arunachal Pradesh, northeastern India - Mitra, Santanu; Payra, Arajush; Chandra, Kailash (Zootaxa, 2018)
A new species of potamid crab of the genus Teretamon Yeo & Ng, 2007, is described from Namdapha Tiger Reserve in Changlang district of Arunachal Pradesh, India. The new species, T. kempi n. sp., can be distinguished from its congeners by a distinct combination of carapace and gonopod characters: a relatively high carapace with a bilobed frontal margin; subquadrate sixth abdominal somite with nearly parallel lateral margins; and a relatively small G1 terminal segment with a semicircular to bluntly triangular dorsal flap. All known Teretamon species are compared with the new species, and a key for this genus is provided.